Developing an integrated Local Culture Padlet Based Writing Course Using Systemic Functional Linguistics Genre Based Pedagogy - Marliza Arsiyana; Sunahrowi Sunahrowi; Suluh Edi Wibowo (Makassar State University, 2023)
Abstract. Due to the implementation of distance learning policy in Indonesia, the usual class is suspended as a response to the COVID-19 pandemic outbreak. Since then, the demand of innovative teaching involving the use of computer assisted learning tools increases progressively. Undeniable, a distance learning scheme has not been able to outperform a conventional face-to-face classroom learning. One of the problems was encountered in Production Écrite Elimentaire (hereafter PEE) class, where lecturers could not monitor students’ writing progress directly. This study aims at developing a Padlet based writing course by integrating local culture using Systemic Functional Linguistic Genre Based pedagogy (SFL-GBP) adopting ADDIE approach. In order to achieve this objective, three lecturers and 32 students were involved to validate the result of Padlet product. This research used two kinds of instruments i.e., an open-ended questionnaire and an experts’ rubric. The open-ended questionnaire was used to identify students’ needs in PEE course, and the experts’ rubric was used to examine Padlet by regarding the appropriateness of material and language, the procedure of SFL-GPB, and the media. The overall mean scores of the experts' judgement towards the Padlet feasibility shows significant figures, i.e., the material aspects gained 3.7, the appropriateness was 3.8, and the media reached 3.7. On the other hand, the results of the students' opinion analysis also show a positive figure where the mean score for material as well as language aspects were 3.9, and media aspect had 3.75 mean score. The findings. The findings of this study were expected to have a further contribution to the development of comprehensive teaching syllabuses, materials, as well as lesson plans for French-language classrooms in the university, especially integrating local culture and the SFL Pedagogy approach. Keywords: Padlet, Writing Course, Local Culture, SFL-GBP